The Role of Magnetic Resonance Imaging in the Planning of Surgical Treatment of Deep Pelvic Endometriosis - Manti, Francesco; Battaglia, Caterina; Bruno, Iennarella; Ammendola, Michele; Navarra, Giuseppe; Currò, Giuseppe; Laganà, Domenico (Frontiers in Surgery, 2022)
Background. To prospectively evaluate the diagnostic accuracy of Magnetic Resonance Imaging (MRI) for the planning of surgical treatment of deep pelvic endometriosis. Materials and Methods. From January 2020 to December 2021, we evaluated 72 patients with symptoms characteristic of endometriosis to plan the appropriate surgical treatment. Sensitivity (Se), specificity (Sp), predictive values (VPP/VPN), and the accuracy of MRI for detection of deep pelvic endometriosis were calculated. Results. Seventy-two patients (mean age, 35.5 years; range, 20 – 46 years) suspected of having pelvic endometriosis were recruited. Pelvic endometriosis was confirmed at pathologic examination in 56 (77.7 %) of 72 patients. Twenty-two (39.3%) of 56 patients were subjected to VLS, and 16 (72.2%) of 22 were treated by surgery. Sensitivity (Se), specificity (Sp), VPP, VPN in intestinal endometriosis diagnosis were respectively 100%, 93.3%, 100%, 87.5%, and diagnostic accuracy 95.4%. MRI Se in ureteral endometriosis diagnosis was 50%, Sp was 100%, VPP was 100%, VPN was 78%, and diagnostic accuracy was 82%. MRI Se in endometrioma diagnosis was 92.3%, Sp was 100%, VPP was 100%, VPN was 90%, and diagnostic accuracy was 95.4%. MRI Se in SRV endometriosis diagnosis was 80%, Sp 100%, VPP 100% VPN 85.7% and diagnostic accuracy 91%. The MRI Se in the diagnosis of endometriosis involving ULS was 100%, Sp 92.8%, VPP 89%, VPN 100%, and diagnostic accuracy 95.4%. Complete concordance results in a 100% result for all calculated values in diagnosing bladder endometriosis localizations. Conclusion. MR imaging demonstrates high accuracy in detecting deep pelvic endometriosis in specific locations. It allows the localization of deep pelvic lesions with highly fibrotic components that are hardly recognizable with other imaging methods and not visible with VLS.